The training effect by force without extreme style ring for the development of some physical abilities and skill level of performance for students strike the front third phase ball Racquet Sports (Tennis) - Farhan, Ahmed; Mhous, Raad (Journal of Physical Education, 2010)
The aim of study is development of sup-maximal strength by circle style to effect in some physical ability and playing four-hand in tennis (control-experimental) sample and knowledge exactly what is effect in them .the hypothesis there are statistical differences between control and experimental favours of the second group in some physical ability and playing four-hand in tennis and some physical ability by using experimental program